STING Agonist Combined to a Protein-Based Cancer Vaccine Potentiates Peripheral and Intra-Tumoral T Cell Immunity - Rossi, Matteo; Carboni, Susanna; Di Berardino-Besson, Wilma; Riva, Erika; Santiago-Raber, Marie-Laure; Belnoue, Elodie; Derouazi, Madiha (Frontiers in Immunology, 2021)
Combining different immunotherapy approaches is currently building the future of immunotherapy, with the view to maximize anti-tumoral efficacy for larger patients population. The KISIMA(TM) platform allows the development of protein-based cancer vaccines able to induce tumor-specific T cell response resulting in anti-tumoral efficacy in various mouse models. Intra-tumoral administration of stimulator of interferon genes agonists (STINGa) was shown to induce a potent inflammatory response leading to the development of tumor-specific immunity. Here, we explored the efficacy and mechanisms of action of subcutaneous STINGa treatment combined with therapeutic vaccination in various mouse tumor models. This combinatory treatment highly enhanced frequency and effector function of both peripheral and intra-tumoral antigen-specific CD8 T cells, promoting potent IFNγ and TNFα production along with increased cytotoxicity. Moreover, combination therapy favorably modulated the tumor microenvironment by dampening immune-suppressive cells and increasing CD4 T cells infiltration together with their polarization toward Th1 phenotype. Combination with STINGa treatment improved the effect of therapeutic vaccination, resulting in a prolonged control and slower growth of B16-OVA and TC-1 tumors. Altogether, the results presented here highlight the potential of combining STINGa with a therapeutic protein vaccine for cancer treatment.